Academic Writing in Times of Crisis: Refashioning Writing Tutor Development for Online Environments - Ganobcsik-Williams, Lisa; Curry, Niall; Neculai, Catalina (Journal of Academic Writing, 2022)
This paper builds on a discussion launched by the EATAW 2021 conference panel, ‘Writing Tutor Development: Challenges and Opportunities in the Current State of the Art’. As a critical discussion of the panel’s themes, the paper engages with academic writing in times of crises by zooming in on infrastructures of writing support, namely the complex system in which Academic Writing Tutoring takes place, contextualised within the Centre for Academic Writing (CAW) at Coventry University, UK. Beginning with a consideration of what constitutes a ‘writing tutor’ in contemporary contexts and at CAW, the paper outlines a range of academic writing support identities and roles, unravels the institutional drivers that shape them, and offers perspectives on reconciling apparently disparate roles. Next, the paper addresses the issue of agency in terms of the challenges of enculturating writing tutors into communities of practice, discourse communities, and research networks. This is done with a view to reflecting on the practices in CAW and beyond, thus demonstrating the need for varied development and support pathways to facilitate the move towards online delivery amid, and after, a time of global crisis, namely, the COVID-19 pandemic. The discussion centres on how challenges can be overcome through sustained professional development, focusing on the role of technology in not only refashioning academic writing support, but also the roles and practices of Academic Writing Tutors at CAW. Issues of digital pedagogies, technologies, and digital literacies permeate this discussion of the online pivot and crisis pedagogies, offering analysis, reflections, and questions to guide future directions in (online) Academic Writing Tutor development and Academic Writing (crisis) Pedagogies research.